Critical care nurses' perceptions of essential elements for an intensive care liaison or critical care outreach nurse curriculum. Issue 4 (July 2022) - Currey, Judy; McIntyre, Tammie; Taylor, Carmel; Allen, Josh; Jones, Daryl
Abstract: Background: For over a decade, patients experiencing clinical deterioration have been attended to by specialised nurses, the most senior of which are intensive care unit liaison nurses (ICU LNs) or critical care outreach nurses. These roles have evolved without consistent and formal recognised educational preparation. To continue to advance patient safety, an understanding of the educational requirements for these vital roles is required. Aim: The aim of this study was to ascertain nurses' perceptions of the curriculum required to perform the roles of ICU LNs or critical care outreach nurses within an acute care sector rapid response system. Methods: An exploratory descriptive study was conducted at an international rapid response system conference in 2016 following ethics approval. Using convenience sampling, extended response surveys were completed by nurses with rapid response system leadership experience and roles. Data were analysed using content analysis according to a priori themes of theoretical knowledge, skills, and attributes. Results: Seventy-seven registered nurses volunteered to take part in the study, forming 14 groups, each with four to seven members. Participants identified key concepts for desired theoretical knowledge, practical skills, and personal attributes. Professional behaviours were more frequently emphasised than theoretical knowledge or practical skills, suggesting personal attributes were highly valued in these leadership roles. Conclusions: A curriculum designed to prepare patient safety leadership roles of the ICU LN or critical care outreach nurse has been identified. These findings can inform the development of postgraduate courses and training requirements, along with position descriptions and expectations of employers regarding the skill set expected in these leadership roles.